2008
DOI: 10.1590/s0102-311x2008001500004
|View full text |Cite
|
Sign up to set email alerts
|

Preterm births, low birth weight, and intrauterine growth restriction in three birth cohorts in Southern Brazil: 1982, 1993 and 2004

Abstract: Three birth cohort studies from 1982, 1993 and 2004, in Pelotas, Southern Brazil provided the data for this study of trends in preterm births, low birth weight, and intrauterine growth restriction. We found a slight increase in the period in the low birth weight prevalence from 9% to 10%. Intrauterine growth restriction decreased from 14.8% in 1982 to 9.4% in 1993, and subsequently increased to 12% in 2004, whereas preterm births increased markedly, from 6.3% in 1982 to 14.7% in 2004. This striking increment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
3
27

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 18 publications
10
69
3
27
Order By: Relevance
“…Furthermore, there was a significant reduction in the proportion of deliveries with a gestational age of 40 weeks or more between 1999 and 2002 in the USA, with a corresponding increase for gestational ages of between 34 and 39 weeks; this was observed both for births following the premature rupture of membranes and for those resulting from medical interventions 2 . Similar increases have been reported in Brazil where three birth cohorts in the city of Pelotas showed that preterm deliveries accounted for 6.3% of all births in 1982, 11.4% in 1993 and 14.7% in 2004 3 . A recent review of Brazilian population-based studies confirmed this increase 4 , which has led to a rising trend in the prevalence of low birth weight babies, and may have had contributed to the lack of success in reducing neonatal mortality in spite of improved care for preterm and low birth weight babies 5 .…”
Section: Introductionsupporting
confidence: 84%
“…Furthermore, there was a significant reduction in the proportion of deliveries with a gestational age of 40 weeks or more between 1999 and 2002 in the USA, with a corresponding increase for gestational ages of between 34 and 39 weeks; this was observed both for births following the premature rupture of membranes and for those resulting from medical interventions 2 . Similar increases have been reported in Brazil where three birth cohorts in the city of Pelotas showed that preterm deliveries accounted for 6.3% of all births in 1982, 11.4% in 1993 and 14.7% in 2004 3 . A recent review of Brazilian population-based studies confirmed this increase 4 , which has led to a rising trend in the prevalence of low birth weight babies, and may have had contributed to the lack of success in reducing neonatal mortality in spite of improved care for preterm and low birth weight babies 5 .…”
Section: Introductionsupporting
confidence: 84%
“…25,29,51,65 Thus, countries with high prevalence of risk factors (such as low maternal body mass index and malaria) with a resulting high prevalence of term LBW are also more likely to present high rates of preterm LBW births. In addition, a number of studies 7,23,28,45,50 show that preterm births are more frequent among poor populations. For these reasons, the current fi ndings are more biologically and epidemiologically plausible than those from earlier studies based on data collected pre-1990, which showed little variation of preterm rates across a wide range of LBW prevalences.…”
Section: Discussionmentioning
confidence: 99%
“…55,57 In addition, selected studies indicate a decreasing prevalence of IUGR in some LMICs 2,7,33 at the same time that others report substantial increases in preterm births. 7,22,27,49 Data from South America suggest that the proportion of preterm LBW babies has increased among LBW births from 59% (1992) to 70% (2000) in Uruguay (PAHO/WHO Latin American Center for Perinatology, unpublished observations) and from 46% (1996) to 62% (2004) in Brazil. 47 The latter trend is confi rmed in Brazilian birth cohort studies in the city of Pelotas, Southern Brazil, where this proportion increased from 60% in 1993 to 68% in 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More methodological details of the study can be found elsewhere. 5,6 The study outcome was report of medicine use regardless of therapeutic indication or class at the three, 12-and 24-month follow-up during a 15-day recall period. Mothers were asked about their children's medicine use in the past 15 days and then medicine names were recorded and prescriptions and packages requested.…”
Section: Methodsmentioning
confidence: 99%